A review of geomagnetically induced current effects on electrical power system: Principles and theory - Abda Z.M.K.; Ab Aziz N.F.; Mohd Zainal Abidin Ab Kadir; Rhazali Z.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Earth (planet); Electric fields; Geomagnetism; Induced currents; Intercalation; Power transformers; Electrical power system; Geomagnetic disturbance; Geomagnetically induced currents; GIC blocking device; Mitigation techniques; Power system components; Power system operators; Technological system; Electric power transmission networks